Comparison of the effects of three endodontic irrigants on the free surface energy of radicular dentin - Habib Rezaee Dehghan; Babak Jaleh; Loghman Rezaee Sofi; Zahed Mohammadi (Isfahan University of Medical Sciences, 2011)
Introduction: Irrigation solutions used in root canal therapy might alter the wettability of root canal dentin, thereby affecting adhesion of dental materials. The aim of this study was to compare the effects of three different endodontic irrigants on the free surface energy of radicular dentin.Materials and Methods: In this in vitro study, 48 extracted human maxillary incisors and canines were used. The middle portion of each root was sectioned longitudinally to prepare an appropriate dentin sample. After polishing and embedding each sample in acrylic blocks, the samples were randomly assigned to 4 groups, and immersed in the following solutions for 10 minutes: group 1: saline solution (control); group 2: 2% (or 0.2%????) chlorhexidine; group 3: 0.25% iodine; group 4: 1% sodium hypochlorite. The samples were then air-dried and the free surface energy of dentin was measured in dyne/cm. Data were analyzed using one-way ANOVA and Tukey test (α=0.05).Results: The means and standard deviations of free surface energy in groups 1 to 4 were 60.87±2.46, 57.54±2.86, 59.83±5.38 and 51.67±2.22, respectively. One-way ANOVA showed significant differences between the groups (p value > 0.001). The results of Tukey test showed that the free surface energy of dentin was significantly lower than other groups after using 1% sodium hypochlorite (p value < 0.001).Conclusion: The results of this study showed that endodontic irrigation solutions, mainly 1% sodium hypochlorite, reduce free surface energy of dentin, adversely affecting adhesion of dental materials to dentin. Key words: Dentin, Endodontic irrigants, Free surface energy, Wettability.